Advanced membrane-based electrode engineering toward efficient and durable water electrolysis and cost-effective seawater electrolysis in membrane electrolyzers - Tang, Jiayi; Su, C.; Shao, Zongping (2024)
Researchers have been seeking for the most technically-economical water electrolysis technology for entering the next-stage of industrial amplification for large-scale green hydrogen production. Various membrane-based electrolyzers have been developed to improve electric-efficiency, reduce the use of precious metals, enhance stability, and possibly realize direct seawater electrolysis. While electrode engineering is the key to approaching these goals by bridging the gap between catalysts design and electrolyzers development, nevertheless, as an emerging field, has not yet been systematically analyzed. Herein, this review is organized to comprehensively discuss the recent progresses of electrode engineering that have been made toward advanced membrane-based electrolyzers. For the commercialized or near-commercialized membrane electrolyzer technologies, the electrode material design principles are interpreted and the interface engineering that have been put forward to improve catalytic sites utilization and reduce precious metal loading is summarized. Given the pressing issues of electrolyzer cost reduction and efficiency improvement, the electrode structure engineering toward applying precious metal free electrocatalysts is highlighted and sufficient accessible sites within the thick catalyst layers with rational electrode architectures and effective ions/mass transport interfaces are enabled. In addition, this review also discusses the innovative ways as proposed to break the barriers of current membrane electrolyzers, including the adjustments of electrode reaction environment, and the feasible cell-voltage-breakdown strategies for durable direct seawater electrolysis. Hopefully, this review may provide insightful information of membrane-based electrode engineering and inspire the future development of advanced membrane electrolyzer technologies for cost-effective green hydrogen production.